The Origins of Habeas Corpus - García Belaunde, Domingo (1973)
This article addresses the evolution and the importance of Habeas Corpus in the protection of individual rights in various political contexts throughout history, from its origins to its incorporation into Peruvian law. Originating in ancient Greek and Roman law, the protection of personal liberty was formalized with the Interdicto de Homine Libero Exhibendo. However this instrument had limited scope, it represented a starting point in creating tools for freedom protection. Based on this, the author explores the institution of habeas corpus in the history of England, the United States, France, Latin America and Peru. The article highlights the origin of habeas corpus in the Magna Carta of 1215 and its consolidation in the Bill of Rights of 1689 in England, and emphasizes its importance in protecting civil liberties and the limitation of state power.  In this regard, the author notes that these English laws are the main precedent in the development of habeas corpus in Latin America. To conclude, he makes a brief review of habeas corpus in Peru, showing the challenges in its adoption until its constitutional consecration in 1920.